Preparation and characterization of materials based on fish scale collagen and polyphenols extracted from Camellia chrysantha - Thuy Chinh, Nguyen; Huynh, Mai Duc; Thi Ngoc Lien, Ly; Mai, Tran Thi; Hoang , Thai (Vietnam Journal of Science and Technology, 2023)
This paper presents the preparation and some characteristics of collagen/polyphenols materials containing different polyphenols contents. Collagen was extracted from fresh-water fish scales and polyphenols were extracted from Camellia chrysantha (Tam Dao, Vinh Phuc, Viet Nam). A comparison between these polyphenols and green tea polyphenols (commercial product) was carried out in this study. Functional groups and morphology of collagen/polyphenols materials were determined by Infrared spectroscopy (IR) and scanning electron microscope (SEM). Ultraviolet-visible spectroscopy (UV-Vis) was used to evaluate the release of polyphenols from collagen/polyphenols materials in simulated body fluids. In addition, the anti-oxidation ability of collagen/polyphenols materials was also investigated by 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging method. The obtained results showed that polyphenols with the size of ca. 100 nm were dispersed and adhered well to the collagen matrix. The release of polyphenols from the materials follows two stages: fast release during the first 2 hours of testing and controlled release in the following hours. The content of polyphenols released from the collagen/polyphenols materials in pH 2.0 solution was higher than that in pH 7.4 solution. After 8 hours of testing, the content of polyphenols released from the collagen/polyphenols materials reached 15-65 % depending on the polyphenols content, type of polyphenols and pH of solution. The anti-oxidation ability of polyphenols extracted from Camellia chrysantha is better than that of green tea polyphenols and collagen/polyphenols materials.